Sourcies of the inactivation kinetic nonlinearity for microorganisms under pressure - Noga, I. V.; Shatalov, V. M. (Biophysical Bulletin, 2007)
The physical reasons of observable deviations of the inactivation kinetics from linearity are analyzed for the high pressure processing of microorganisms in food samples. It is shown, that insignificant heating of samples by compression leads under some conditions to increase of the reaction rate constant from 2 up to 5 times. Solving the heat transfer equation the deviations from the linear law, arising due to non-uniform cooling of the sample during of the pressure processing are calculated. It is shown, that the kinetic curves received within the framework of the linear equation model might have nonlinear biphasic character due at account of cooling. Amendments to inactivation curves for MAFAM are estimated. It is drawn a conclusion that deviations from linearity can arise within the linear model at the account of non-stationary spatially non-uniform distribution of temperature inside of the sample.